2017
DOI: 10.1097/mib.0000000000001143
|View full text |Cite
|
Sign up to set email alerts
|

Transmural Healing Is Associated with Improved Long-term Outcomes of Patients with Crohnʼs Disease

Abstract: TH is associated with improved long-term outcomes in Crohn's disease and may be a more suitable target than MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
130
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(144 citation statements)
references
References 21 publications
4
130
2
1
Order By: Relevance
“…Overall, our data are in line with Fernandes et al recent publication showing that complete transmural healing is associated with improved long‐term outcomes in CD. Our data support the notion that specific components of the persistent damage may be linked to long‐term disease outcomes, in both clinical practice and clinical trials, such as the need of hospitalisation or surgical resection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, our data are in line with Fernandes et al recent publication showing that complete transmural healing is associated with improved long‐term outcomes in CD. Our data support the notion that specific components of the persistent damage may be linked to long‐term disease outcomes, in both clinical practice and clinical trials, such as the need of hospitalisation or surgical resection.…”
Section: Discussionmentioning
confidence: 99%
“…While mucosal healing as assessed by ileocolonoscopy has been studied in depth, few studies have evaluated the characteristics of transmural healing assessed by means of MRE . Of note, residual mural abnormalities, such as wall thickening, or extramural lesions, like creeping fat, can persist in intestinal segments with endoscopic remission . From the clinical point of view, it is crucial to determine whether these lesions represent established persistent damage (likely irreversible) or an inflammatory component that can heal with appropriate anti‐inflammatory therapy …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond mucosal healing, histological remission may be associated with improved outcomes 121 122. Furthermore, small studies have shown that normalisation of bowel wall thickness on MRE, or ‘transmural healing’, may be superior to endoscopic healing alone 123. GIUS holds promise as a useful tool to evaluate transmural healing in IBD longitudinally, although further studies are required to validate the prognostic significance of transmural healing before it can be considered a treatment target.
Future roles of GI ultrasound (GIUS)

Preliminary data suggest elastography can aid in differentiating inflammation from fibrosis in stricturing bowel disease (evidence level 4).

Functional bowel ultrasonography may be helpful in identifying intestinal dysmotility in functional bowel disorders (evidence level 4).

GIUS is conceptually a useful tool for IBD activity assessment in pregnancy, although data are lacking (evidence level 5).

GIUS may be a useful tool to evaluate transmural healing in IBD, the prognostic significance of which requires further validation (evidence level 5).

…”
Section: How To Position Gius In Ibd Clinical Practice?mentioning
confidence: 99%